Insight into the Family of Na+/Ca2+ Exchangers of Caenorhabditis elegans - Sharma, Vishal; He, Chao; Sacca-Schaeffer, Julian; Brzozowski, Eric; Martin-Herranz, Daniel E; Mendelowitz, Zelda; Fitzpatrick, David A; O’Halloran, Damien M (Genetics (Austin), 2013)
Here we provide the first genome-wide in vivo analysis of the Na+/Ca2+ exchanger family in the model system Caenorhabditis elegans. We source all members of this family within the Caenorhabditis genus and reconstruct their phylogeny across humans and Drosophila melanogaster. Next, we provide a description of the expression pattern for each exchanger gene in C. elegans, revealing a wide expression in a number of tissues and cell types including sensory neurons, interneurons, motor neurons, muscle cells, and intestinal tissue. Finally, we conduct a series of behavioral and functional analyses through mutant characterization in C. elegans. From these data we demonstrate that, similar to mammalian systems, the expression of Na+/Ca2+ exchangers in C. elegans is skewed toward excitable cells, and we propose that C. elegans may be an ideal model system for the study of Na+/Ca2+ exchangers.